Teori dan Aplikasi Pemikiran Kontemporer dalam Pembaharuan Hukum Keluarga Islam - Ramadhan, Muhammad Khairi; Ananda, Faisar; Irwansyah, Irwansyah (VISA: Journal of Vision and Ideas, 2025)
Islamic family law offers to resolve several problems, because family law is considered the core of sharia. In essence, it is not intended to teach Muslims so that later in marriage they can practice it, but the law here is solution in nature, meaning that Islamic law provides solutions in resolving family problems that occur. However, sometimes, existing laws cannot be understood regarding their wisdom and philosophy, resulting in the perception that Islamic law is no longer representative in resolving Islamic family civil cases.